2016
DOI: 10.3389/fnhum.2016.00080
|View full text |Cite
|
Sign up to set email alerts
|

Seizure Prediction and Detection via Phase and Amplitude Lock Values

Abstract: A robust seizure prediction methodology would enable a “closed-loop” system that would only activate as impending seizure activity is detected. Such a system would eliminate ongoing stimulation to the brain, thereby eliminating such side effects as coughing, hoarseness, voice alteration, and paresthesias (Murphy et al., 1998; Ben-Menachem, 2001), while preserving overall battery life of the system. The seizure prediction and detection algorithm uses Phase/Amplitude Lock Values (PLV/ALV) which calculate the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 38 publications
(42 reference statements)
2
42
0
Order By: Relevance
“…[7] The adjustment of the selfexcited dust acoustic wave mode to match the externally applied modulation is a nonlinear process known as (phase) synchronization; a process that is ubiquitous in a variety of physical systems and is believed to play an important role in many self-organized phenomena. [8][9][10][11][12][13] In this paper, we present a measurement showing the volumetric nature of this synchronization process by applying a time-resolved Hilbert Transform [14,15] to high-speed imaging of the dust acoustic wave in an rf glow discharge plasma.…”
Section: Introductionmentioning
confidence: 99%
“…[7] The adjustment of the selfexcited dust acoustic wave mode to match the externally applied modulation is a nonlinear process known as (phase) synchronization; a process that is ubiquitous in a variety of physical systems and is believed to play an important role in many self-organized phenomena. [8][9][10][11][12][13] In this paper, we present a measurement showing the volumetric nature of this synchronization process by applying a time-resolved Hilbert Transform [14,15] to high-speed imaging of the dust acoustic wave in an rf glow discharge plasma.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, noises and interferences are closely related to the patients, which needs expensive manual processing even if this is currently only feasible in theory. 13 Basically, there exists no general solution to reliable EEG denoising. • In the context of conventional EEG classification, denoising of high quality is a prerequisite for feature extraction.…”
Section: Discussionmentioning
confidence: 99%
“…However, sufficient a priori knowledge is often required to effectively separate noises and interferences from the weak signal, without which, the original intrinsic information of EEG could be lost or destroyed. In most cases, noises and interferences are closely related to the patients, which needs expensive manual processing even if this is currently only feasible in theory . Basically, there exists no general solution to reliable EEG denoising. In the context of conventional EEG classification, denoising of high quality is a prerequisite for feature extraction .…”
Section: Introductionmentioning
confidence: 99%
“…Similar intervals have been considered in [ 38 , 51 , 52 ]. Based on literature, it has been reported that there are electrophysiological changes, which might develop minutes to hours before the actual seizure onset [ 38 , 47 , 54 ]. Therefore, the preictal training data could be selected from any of the following options: Preictal-0: the preictal training interval ends right at the beginning of seizure onset.…”
Section: Methodsmentioning
confidence: 99%
“…Note that the data segment preceding the seizure onset is called the preictal interval and ranges from a few seconds to several hours long [ 38 , 47 , 54 ]. The performance of the proposed predictor is compared with the random and Poisson predictors and with existing sEEG-based prediction methods [ 17 , 18 , 28 , 41 , 45 , 47 , 48 , 54 , 55 ]. The results show that the proposed prediction method could be of potential value for early warnings for epileptic patients and/or their caregivers.…”
Section: Introductionmentioning
confidence: 99%